Tornado Seasonality in Central‐Southern Chile - V. Caballero‐Morán; R. Rondanelli (Geophysical Research Letters)
Abstract Tornado records in Chile show an apparent seasonality with a peak between May and June. We study this seasonality in central‐south and austral Chile by analyzing three indicators of tornado environments: vorticity generation parameter (VGP), storm‐relative helicity (SRH) and mean relative humidity RH‾. Annual cycles of VGP, SRH and RH‾ show favorable conditions during the fall in the central‐south region, well correlated with the records in the area, and associated with maximum values of low‐level (0–1 km) and deep‐layer (0–6 km) wind shear, and relatively high values of most unstable CAPE. In the austral region, favorable conditions occur during the summer, in the presence of maximum deep‐layer wind shear and maximum values of the most unstable CAPE. Analysis of temperature, wind, and humidity were performed to understand the mechanisms that lead to the development of these conditions in these two regions.